Foreign Direct Investment Inflows and the Industrialization of African Countries - (:unkn) unknown (My University, 2015)
This paper examines the relationship between inward foreign direct investment (FDI) and the industrialization process inAfrica. It uses panel data from 49 countries over the period of 1980–2009. The results indicate that FDI did not have a significant impacton the industrialization of these countries, while other variables, such as the size of the market, the financial sector, and internationaltrade were important. This study concludes that the role of FDI in the transformation agenda, which is currently being discussed inAfrica, should be carefully analyzed to maximize the impact of these capital inflows.
Keywords: African Research